Computational simulation of the cupula behavior in vestibular pathologies of the inner ear - Santos, Carla (2019)
Vertigo is reported as one of the most common symptoms in the world, commonly related with vestibular disorders. It is considered the third most frequent complaint in medicine, transmitting a sense of inadequacy and insecurity, mainly in elders. The aim of this work is to contribute to a better understanding on how the vestibular system works, mainly during vestibular rehabilitation process. This knowledge will help in the development of new techniques that will facilitate a more efficient rehabilitation. Vestibular rehabilitation consists in a set of exercises, known as maneuvers, that can reduce and even eliminate the symptoms of dizziness and imbalance associated with a vestibular disorder.